A novel truncating variant within exon 7 of KAT6B associated with features of both Say–Barber–Bieseker–Young–Simpson syndrome and genitopatellar syndrome: Further evidence of a continuum in the clinical spectrum of KAT6B‐related disorders. Issue 2 (11th December 2017) - Marangi, Giuseppe; Di Giacomo, Marilena C.; Lattante, Serena; Orteschi, Daniela; Patrizi, Sara; Doronzio, Paolo N.; Riviello, Francesco N.; Vaisfeld, Alessandro; Frangella, Silvia; Zollino, Marcella
Abstract : KAT6B sequence variants have been identified in both patients with the Say–Barber–Biesecker–Young–Simpson syndrome (SBBYSS) and in the genitopatellar syndrome (GPS). In SBBYSS, they were reported to affect mostly exons 16–18 of KAT6B, and the predicted mechanism of pathogenesis was haploinsufficiency or a partial loss of protein function. Truncating variants in KAT6B leading to GPS appear to cluster within the proximal portion of exon 18, associated with a dominant‐negative effect of the mutated protein, most likely. Although SBBYSS and GPS have been initially considered allelic disorders with distinctive genetic and clinical features, there is evidence that they represent two ends of a spectrum of conditions referable as KAT6B‐ related disorders. We detected a de novo truncating variant within exon 7 of KAT6B in a 8‐year‐old female who presented with mild intellectual disability, facial dysmorphisms highly consistent with SBBYSS, and skeletal anomalies including exostosis, that are usually considered component manifestations of GPS. Following the clinical diagnosis driven by the striking facial phenotype, we analyzed the KAT6B gene by NGS techniques. The present report highlights the pivotal role of clinical genetics in avoiding clear‐cut genotype‐phenotype categories in syndromic forms of intellectual disability. In addition, it further supports the evidence that a continuum exists within the clinical spectrum of KAT6B ‐associated disorders.